On the maximal operator of (C, α)-means of Walsh–Kaczmarz–Fourier series - Goginava, U.; Nagy, K. (Український математичний журнал, 2010)
Simon [J. Approxim. Theory, 127, 39–60 (2004)] proved that the maximal operator σα,κ,* of the (C, α)-means of the Walsh–Kaczmarz–Fourier series is bounded from the martingale Hardy space H p to the space L p for p > 1 / (1 + α), 0 < α ≤ 1. Recently, Gát and Goginava have proved that this boundedness result does not hold if p ≤ 1 / (1 + α). However, in the endpoint case p = 1 / (1 + α ), the maximal operator σα,κ,* is bounded from the martingale Hardy space H 1/(1+α) to the space weak- L 1/(1+α). The main aim of this paper is to prove a stronger result, namely, that, for any 0 < p ≤ 1 / (1 + α), there exists a martingale f ∈ H p such that the maximal operator σα,κ,* f does not belong to the space L p . Саймон довів [див. J. Approxim. Theory. - 2004. - 127. - P. 39 - 60], що максимальний оператор σα,κ,∗ (C,α)-середніх рядів Уолша - Качмажа - Фур'є є обмеженим з мартингального простору Харді Hp до простору Lp для p>1/(1+α),0<α≤1. Нещодавно Гат і Гогінава довели, що цей результат про обмеженість не виконується, якщо p≤1/(1+α). Однак у випадку кінцевої точки p=1/(1+α) максимальний оператор σα,κ,∗ к обмеженим з мартингального простору Харді H1/(1+α) до простору слабкого L1/(1+α). Головна мета даної статіі —довести більш вагомий результат, тобто довести, що для будь-якого 0<p≤1/(1+α) існує мартингал f ∈ Hp такий, що максимальний оператор σα,κ,∗f не належить простору Lp.